Low-Cytotoxicity Fluorescent Probes Based on Anthracene Derivatives for Hydrogen Sulfide Detection - Shang, Xuefang; Li, Jie; Feng, Yaqian; Chen, Hongli; Guo, Wei; Zhang, Jinlian; Wang, Tianyun; Xu, Xiufang (Frontiers in Chemistry, 2018)
Owing to the role of H2S in various biochemical processes and diseases, its accurate detection is a major research goal. Three artificial fluorescent probes based on 9-anthracenecarboxaldehyde derivatives were designed and synthesized. Their anion binding capacity was assessed by UV-Vis titration, fluorescence spectroscopy, HRMS, 1HNMR titration and theoretical investigations. Although the anion-binding ability of compound 1 was insignificant, two compounds 2 and 3, containing benzene rings, were highly sensitive fluorescent probes for HS− among the various anions studied (HS−, F−, Cl−, Br−, I−, AcO−, H2PO4−, SO32−, Cys, GSH and Hcy). This may be explained by the nucleophilic reaction between HS− and the electron-poor C=C double bond. Due to the presence of a nitro group, compound 3, with a nitrobenzene ring, showed stronger anion binding ability than that of compound 2. In addition, compound 1 had a proliferative effect on cells, and compounds 2 and 3 showed low cytotoxicity against MCF-7 cells in the concentration range of 0–150 μg·mL–1. Thus, compounds 2 and 3 can be used as biosensors for the detection of H2S in vivo and may be valuable for future applications.